Levels and ecological risk of heavy metals in the surface sediments of tidal flats along the North Jiangsu coast, China. (September 2021) - Shu, Qiang; Ma, Yanyu; Liu, Qing; Zhang, Shunjie; Hu, Zhou; Yang, Peipei
Abstract: We investigated the contamination levels of nine heavy metals (Mn, Pb, V, Cr, Co, Ni, Cu, Zn, and As) in 153 surface sediment samples collected along five tidal flats on the North Jiangsu coast, China. The spatial distributions of most heavy metals gradually decreased from the northern Sheyang region to the southern Jianggang region, while slightly increasing in the Rudong region. Principal component analysis indicated that Co, Ni, Cu, Zn, and As were mainly derived from the natural environment, V and Cr were mainly derived from human activities. Additionally, Mn and Pb influenced by both natural and human sources. The geo-accumulation index and the contamination factor indicated that heavy metal contamination in the sediments exhibited little to no pollution levels. The potential ecological risk index exhibiting low ecological risks. Meanwhile, the mean probable effect level quotient values indicating slight toxicity. Cr and Ni were the major contributors to toxicity. Graphical abstract: Unlabelled Image Highlights: Heavy metal contamination in surface sediments of North Jiangsu Coast belongs to light pollution or no pollution The ecological risk of heavy metals is low in the surface sediments of North Jiangsu coast Mn, Pb, Co, Ni, Cu, Zn, and As mainly come from the natural environment; V and Cr mainly come from human activities